Diseño y puesta en marcha de un sistema de control para una freidora industrial a gas (2021)
This document presents the automation of the ignition mechanism, temperature control, and systematization of the cooking process of the industrial gas fryer FT-50G, TORNADO brand. In the first place, main characteristics and mechanisms used in prototypes similar to the fryer under investigation are described, which, together with the results and analysis of surveys carried out with end-users, on factors that the handling of the industrial fryer, allowed to define the aspects related to the mechanical system, control design and electronic design of the industrial fryer. The basic concepts and technical foundations necessary for the development of this work are found in chapter 2. While in chapters 3, 4, and 5 the mechanical system, control design, and electronic design are detailed, respectively. Finally, the execution of the assembly and start-up of the prototype is exposed in chapter 6, where the reduction of risk for the end-user is highlighted, obtaining a reliable and competitive product in the national food industry